Europejski Fundusz Rozwoju Regionalnego jako instrument polityki regionalnej UE a absorpcja pomocy dla Polski na lata 2004-2006 - Kociszewska, Irena; Pańczak, Agata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The main conclusion of the paper is that the adequate regional policy directed to deepen the economic and social convergence and to increase the competitiveness of the region and well-oriented personnel structure are the ways to better absorption of structural funds for development programes. These aspects are the background for "The National Development Programme", which integrates sector policies. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1147, s. 212-226